Teaching Microcontrollers with the MSP430 - Santos, H. (2019)
•Why MSP430 in classes •Choosing development tools •Microprocessor teaching at UBI •Microprocessor introduction •Examples of microprocessor usage in other classes •Advanced microprocessor applications